KAT6B Genetic Variant Identified in a Short Stature Chinese Infant: A Report of Physical Growth in Clinical Spectrum of KAT6B-Related Disorders - Zhu, Liuyan; Lv, Lina; Wu, Dingwen; Shao, Jie (Frontiers in Pediatrics, 2020)
Say-Barber-Biesecker-Young-Simpson syndrome (SBBYSS, OMIM #603736) and genitopatellar syndrome (GTPTS, OMIM #606170), characterized by global developmental delay/intellectual disability and special clinical manifestations, are two distinct clinically overlapping syndromes caused by truncating sequence variants in the KAT6B(10q22.2) gene. We detected a de novo heterozygous variant within exon 16 of KAT6B (Chr10p: 76781966-76781967) in a 7-month-old female infant who showed symptoms of short stature, global developmental delay, blepharophimosis and lacrimal duct anomalies highly consistent with SBBYSS. Following the clinical features, we analyzed the KAT6B gene by Next Generation Sequencing (NGS) techniques. Her parents didn’t present the same genetic variant. The patient we reported here is mainly characterized by syndromic forms of short stature and developmental delay. It may contribute to the understanding of the clinical genetics for KAT6B-associated disorders.